2012
DOI: 10.1021/ie302303x
|View full text |Cite
|
Sign up to set email alerts
|

Poly(4-vinylaniline)-Polyaniline Bilayer-Modified Stainless Steels for the Mitigation of Biocorrosion by Sulfate-Reducing Bacteria (SRB) in Seawater

Abstract: A novel strategy by combination of surface-initiated atom transfer radical polymerization (ATRP) and in situ chemical oxidative graft polymerization was employed to tether stainless steel (SS) with poly(4-vinylaniline)-polyaniline (PVAn-PANI) bilayer coatings for mitigating biocorrosion by sulfate-reducing bacteria (SRB) in seawater. A trichlorosilane coupling agent was first immobilized on the SS surfaces to provide sulfonyl halide groups for surface-initiated ATRP of 4-VAn. A subsequent grafting of PANI onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…It is very promising to see that almost 90% of cells were viable on BC/PVAN/PANI composites. Further, an observable higher number of cells on BC/PVAN composites indicates PVAN provides good support for cell proliferation, which could be attributable to the improved hydrophilic properties (Yuan et al, 2012). This suggests that the composites, in particular, PVAN/PANI functionalized BC with enhanced conductivity do not cause any cytotoxicity.…”
Section: Cytocompatibility With Svz Cellsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is very promising to see that almost 90% of cells were viable on BC/PVAN/PANI composites. Further, an observable higher number of cells on BC/PVAN composites indicates PVAN provides good support for cell proliferation, which could be attributable to the improved hydrophilic properties (Yuan et al, 2012). This suggests that the composites, in particular, PVAN/PANI functionalized BC with enhanced conductivity do not cause any cytotoxicity.…”
Section: Cytocompatibility With Svz Cellsmentioning
confidence: 96%
“…As one of the most studied ICPs, polyaniline (PANI) is easily synthesized and possesses a high environmental stability, with simple doping/dedoping chemistry (Huanhuan Wang et al, 2012). On account of this finding, it has been invariably utilized as electrical conductors (Yan, Sada, & Toshima, 2002), batteries (L. Hu, Ren, Yang, & Xu, 2014), sensors (Langer et al, 2004), actuators (Smela, Lu, & Mattes, 2005), electromagnetic shielding (Gupta, Singh, Mathur, & Dhakate, 2014), antistatic coatings (Soto-Oviedo, Araújo, Faez, Rezende, & De Paoli, 2006), corrosion protection (Mirmohseni & Oladegaragoze, 2000;Yuan et al, 2012), and electro-optic and electrochromic devices (Shi et al, 2012). However, pure PANI is typically obtained as an intractable powder that largely hinders its uses in order to fully exploit its functional potentials (Valentová & Stejskal, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The biocorrosion inhibition level of PANI-PVA matrix was analyzed using sulphate reducing Desulphovibrio sp. Yuan et al (2012) also observed that PVAn-PANI bilayer coating is having good corrosion inhibition against SRB. The corrosion rate of uncoated sterile and SRB containing steel coupon were analyzed in various days (Table 2 and Figure 2) and the corrosion rate were ame study w easing corros 4).…”
Section: Biocorrosion Inhibition By Pani-pva Matrixmentioning
confidence: 78%
“…Comparing the antibacterial activity of chitosan and its derivatives indicated that chitosan (compound II) was more effective than its derivatives against several bacteria: C. albicans, E. coli, E. faecalis, and S. aureus. Yuan et al (2012) attempted to reduce biocorrosion by sulfate-reducing bacteria. This approach involved a combination of surface-initiated atom transfer radical polymerization and in situ chemical oxidative graft polymerization techniques.…”
Section: Electrochemically Activated Biocidesmentioning
confidence: 99%